Newly Onset Optic Disc Pit Maculopathy (ODP-M) in a Patient With Primary Angle-closure Glaucoma (PACG) After Surgical Iridectomy: A Case Report. Issue 6 (June 2020) - Li, Cheng; Guo, Congcong; Yang, Yangfan; Yu, Minbin; Ge, Jian; Fan, Zhigang
Abstract : Optic disc pit maculopathy (ODP-M) is a subtype of ODP, characterized by a serous retinal detachment and/or macular retinoschisis. Currently, ODP and ODP-M pathogenesis remain unknown although many hypotheses exist about their clinical features. In this study, we report a case of new ODP-M detected after surgical iridectomy in a patient with primary angle-closure glaucoma (PACG) with a preoperative normal retina and optic nerve. Fine optic disc and the macular area structures were investigated using several imaging techniques. Findings revealed that the course of ODP and ODP-M provide us with some insights and understanding of their underlying pathogenesis. Abstract : Supplemental Digital Content is available in the text.